Addressing the unmet needs in patients with type 2 inflammatory diseases: when quality of life can make a difference - Gómez de la Fuente, Enrique; Alobid, Isam; Ojanguren, Iñigo; Rodríguez-Vázquez, Virginia; Pais, Beatriz; Reyes, Víctor; Espinosa, Miriam; Luca de Tena, África; Muerza, Irantzu; Vidal-Barraquer, Eduard (Frontiers in Allergy, 2023)
Background Patients with asthma (AS), atopic dermatitis (AD), allergic rhinitis (AR), eosinophilic esophagitis (EoE), chronic rhinosinusitis with nasal polyps (CRSwNP), chronic urticaria (CU), non-steroidal anti-inflammatory drugs-exacerbated respiratory disease (N-ERD), and certain phenotypes of chronic obstructive pulmonary disease (COPD), among others, have a common underlying pathogenesis known as Type 2 inflammation (T2i). These diseases often coexist with other T2i conditions and have a substantial impact on the quality of life (QoL) of patients. However, limited data on patients’ experiences, perspectives, and current management of T2i diseases have been published thus far. Aims This survey, promoted by the patient-driven T2i Network Project, aimed at identifying the common drivers and challenges related to the QoL of patients with T2i diseases by putting the patient's perspective at the force and including it in the design of new care strategies. Methodology An anonymous online survey was carried out through convenience sampling between May and June 2023. The survey was codesigned by members of different patient associations, healthcare professionals and healthcare quality experts, and implemented using EUSurvey and distributed through eight patient associations from Spain. The survey consisted of 29 questions related to the participant's sociodemographic features, a series of self-reported multiple choice or rating scale questions, including diagnosis, QoL measures, disease severity, healthcare resource utilization, and quality of care. Results The survey included 404 participants, members from eight patient associations, the majority of whom had moderate-to-severe self-reported disease severity (93%) and one or more coexisting pathologies related to T2i (59%). Patients with more than one pathology had a significantly greater impact on QoL than those with only one pathology (p < .001). Participants with self-reported severe symptoms reported significantly worse QoL than those with mild-to-moderate severity (p < .001). More than half of the patients (56%) felt constantly bothered by the unpredictability of their illness caused by potential exposure to known or unknown disease triggers. The lack of coordination between specialists and primary care was also expressed as an area of dissatisfaction by participants, with 52% indicating a complete lack of coordination and 21% indicating an average coordination. Conclusion This article reports the initial findings of a patient-led initiative, which highlights the common QoL challenges faced by individuals with type 2 inflammation-related diseases and emphasizes the importance of further clinical research to improve the management of this patient group. Considering the significant impact on QoL, a multidisciplinary approach integrated into new healthcare protocols has the potential to improve patient management and QoL, shorten the time to diagnosis and reduce healthcare resource utilization.